Obesity and contraception. (February 2008) - Gupta, Sunanda
Obesity is an important public health issue in England and Wales and is a predictor of mortality in women. In the USA and UK the epidemic of obesity is worsening. In the USA, 33% of the population is obese and obesity causes 400, 000 deaths every year. In England and Wales, nearly two-thirds of women and half of men are overweight. This article reviews this modern epidemic, the impact of obesity on contraceptive choices women make, the efficacy of contraceptive methods, the association (whether causal or otherwise) between obesity, weight gain and hormonal contraception and the relationship between obesity and adverse events in contraceptive users.